2010
DOI: 10.1161/circheartfailure.109.900076
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Precision in the Optimization of Cardiac Resynchronization Therapy

Abstract: Background Cardiac resynchronization therapy improves morbidity and mortality in appropriately selected patients. Whether atrioventricular (AV) and interventricular (VV) pacing interval optimization confers further clinical improvement remains unclear. A variety of techniques are used to estimate optimum AV/VV intervals; however, the precision of their estimates and the ramifications of an imprecise estimate have not been characterized previously. Methods and Results An objective methodology for quantifying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 41 publications
3
17
1
Order By: Relevance
“…The availability of this information has the potential to guide optimization of CRT and device programming. Optimization of device programming is frequently not pursued by practitioners, in large part due to lack of effective tools and methodologies (19). EWI could be uniquely positioned to provide critical information for these purposes, given that it is noninvasive, non-ionizing, low-cost, and can be readily implemented in most ultrasound scanners already available at the point of care.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of this information has the potential to guide optimization of CRT and device programming. Optimization of device programming is frequently not pursued by practitioners, in large part due to lack of effective tools and methodologies (19). EWI could be uniquely positioned to provide critical information for these purposes, given that it is noninvasive, non-ionizing, low-cost, and can be readily implemented in most ultrasound scanners already available at the point of care.…”
Section: Discussionmentioning
confidence: 99%
“…Mokrani et al demonstrated a difference in the optimal AV delay at rest and on exercise depending on whether LVOT VTI or maximum LVFT was employed. (10) Using the iterative method, the exact mechanism that the operator is attempting to manipulate, (timing of ventricular filling) is viewed directly, rather than employing a surrogate outcome measure such as LVOT VTI, which is subject to significant variation due to small changes in the angle between the incident ultrasound beam and the outflow tract with respiration, an effect particularly exaggerated during exercise (23,24). As the maximum improvement in cardiac output with AV delay optimization is in the region of 15-20% (1), any technique with a reported reproducibility of 4-10% during optimal resting conditions should be interpreted with caution during exercise, and may underlie the reported mixed results using these methods (5,6,10).…”
Section: Discussionmentioning
confidence: 99%
“…This optimization has relied so far mostly on the experience of the cardiologist, and echocardiography measurements. It has been shown recently though that even echocardiographic data, thought to be the non-invasive ‘gold-standard’, does not lead to reliable tuning [26]. …”
Section: Applicationsmentioning
confidence: 99%